Who Is Interested in Purchasing Smart Irrigation Systems? - Hayk Khachatryan; Alicia Rihn; Caroline Warwick; Michael Dukes (EDIS)
Water scarcity concerns have led to revolutionary new smart technologies for residential landscape irrigation, including evapotranspiration and soil-moisture sensor systems. The adoption of smart irrigation technologies into residential landscapes, however, has been slow. This 7-page publication written by Hayk Khachatryan, Alicia Rihn, Caroline R. Warwick, and Michael Dukes and published by the UF/IFAS Food and Resource Economics Department provides an overview of how different consumer groups perceive smart irrigation technology and the best promotions to encourage smart irrigation adoption in home landscapes. It is designed for landscapers, irrigation specialists, and marketing professionals who work with and are interested in promoting smart irrigation technologies to end consumers. Firms can use the results to tailor marketing strategies to target relevant customer segments and create promotions to encourage homeowners to adopt water-saving irrigation technologies. http://edis.ifas.ufl.edu/fe1069